KETERKAITAN MENGENAI KEPEMILIKAN AKSES BIG DATA TERHADAP HUKUM PERSAINGAN USAHA - Andriyanto Andriyanto; Ariawan Gunandi (Jurnal Hukum Adigama, 2021)
Along with the development of the times which of course increasingly sophisticated technology as like today, bringing us into the era of revolution 4.0. One of the important components for developments in this era of industry is the presence of Big Data. This Big Data is widely used by companies in business to be able to get a clear picture of consumer behavior and analyze the data to be able to draw the conclusions and also what consumers need in the market. And this of course gonna give a company more access to the market channels in many ways. Unfortunately, this way has the potential to make some company who has access to big data have a dominant position in the market which can lead to monopolization of the market and control over market share. The purpose of this conceptual article is to provide an overview of big data from a competition law perspective and provide advice to the authorities to regulate and supervise the ownership of company access to Big Data that can potentially create a monopolistic market.